Brian's return - Paulsen, Gary. (New York : Dell Laurel-Leaf, 2001)
After his experiences surviving alone in the Canadian wilderness, sixteen-year-old Brian finds it increasingly difficult to live as a normal high school student and begins planning to return to the place where he feels he really belongs.
Pub Weekly.
School Library Journal.
Wilson's Junior High School.
5.3
5-8
Keywords: Self-reliance -- Fiction; Survival -- Fiction; Wilderness areas -- Canada -- Fiction; Self-reliance -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Wilderness areas -- Canada -- Fiction